AI-Augmented Reality: Bridging the Gap between Virtual and Physical Worlds in Real-Time - Parvatha, Nagaraj (International Journal of Scientific Research and Management (IJSRM), 2024)
Artificial Intelligence combined with Augmented Reality creates live connections of virtual content to real environments that changes how people use technology. AI-AR systems combine modern vision systems, learning technologies and edge processing to make smart adaptable interactions across multiple business sectors. These advanced technologies help industries and everyday users work better while creating more precise customized results. Our research dives into the joint work of AI algorithms and AR screens that enable decisions to occur instantly. Our research focuses on AI capabilities such as object scanning, language processing, and distribution systems to explain why AI makes AR systems more effective. Our research shows AI-AR systems overcome technology barriers to deliver real-time intelligent environments for better responses and personalization options. The research examines both the specific advantages and general modifications AI-AR technology can create when integrating virtual content into actual daily experiences. Through research and industry examples this analysis reveals AI-AR technology will enable new opportunities in education, retail, healthcare, and manufacturing sectors. Thanks to AI-AR technology our daily life and industrial progress will see immersive intelligent experiences as a standard part of our future.